2021
DOI: 10.1101/2021.02.24.432720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dichotomous regulation of lysosomes by MYC and TFEB controls hematopoietic stem cell fate

Abstract: It is critical to understand how quiescent long-term hematopoietic stem cells (LT-HSC) sense demand from daily and stress-mediated cues and transition into bioenergetically active progeny to differentiate and meet these cellular needs. Here, we show that lysosomes, which are sophisticated nutrient sensing and signaling centers, are dichotomously regulated by the Transcription Factor EB (TFEB) and MYC to balance catabolic and anabolic processes required for activating LT-HSC and guiding their lineage fate. TFEB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
4
10
0
Order By: Relevance
“…Next, BFP + GFP + PLAG1-S and c-MYC co-overexpressing Lin − CD34 + cells and their control counterparts were assessed for primitive cell maintenance ex vivo ( Figure 7B-C ). Consistent with other reports, 56,90-92 relative to control, ectopic c-MYC independently promotes hematopoietic differentiation, as measured by loss of CD34 + and gain of CD33 + cells ( Figure 7D-E , purple vs red). Over culture c-MYC OE cells also become enlarged relative to control ( Figure 7F , purple vs red) and display the highest rates of active translation ( Figure 7G ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Next, BFP + GFP + PLAG1-S and c-MYC co-overexpressing Lin − CD34 + cells and their control counterparts were assessed for primitive cell maintenance ex vivo ( Figure 7B-C ). Consistent with other reports, 56,90-92 relative to control, ectopic c-MYC independently promotes hematopoietic differentiation, as measured by loss of CD34 + and gain of CD33 + cells ( Figure 7D-E , purple vs red). Over culture c-MYC OE cells also become enlarged relative to control ( Figure 7F , purple vs red) and display the highest rates of active translation ( Figure 7G ).…”
Section: Resultssupporting
confidence: 92%
“…(C) Change in variance-stabilizing transformed (vst) PLAG1 transcript expression in Lin − cord blood cells cultured for 2 or 4 days showing the P value from 1-tailed Student t -test 39 and in 72-hour cultured long-term (Lin − CD34 + CD38 − CD45RA − CD90 + CD49f + ) CB HSCs showing the P value from 1-tailed Student t -test and differential expression from DEseq analysis. 56 (D) Schematic of Lin − CD34 + CB HSPC in vitro and in vivo functional assay timelines and lentivectors used for overexpression of PLAG1 protein isoforms. (E) Primary CFU output by BFP + Lin − CD34 + cells overexpressing PLAG1-A, B, or S, or Luciferase control (n = 3 per experiment).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As many of the upregulated gene sets following miR-130a OE were related to HSC programs, we performed GSEA using quiescent and activated HSC signatures (Forsberg et al, 2010) and observed enrichment of mitotic cell cycle activation and proliferation gene sets and depletion of quiescent genes with miR-130a OE (Figure 2F, S2E). We also observed significant enrichment of MYC targets following miR-130a OE (Figure 2F), consistent with HSC activation and quiescence exit (García-Prat et al, 2021; Laurenti et al, 2008). To determine whether miR-130a alters proliferation and cell cycle kinetics of HSC, we performed EdU incorporation assays utilizing fluorescently-labelled thymidine analog to measure nascent DNA synthesis in sorted LT-HSC and ST-HSC 3 days after transduction with control or miR-130a lentiviruses.…”
Section: Resultssupporting
confidence: 71%
“…Further supporting the molecular features of dormant cells, the IBα KO LT-HSCs also express significantly higher levels of the transcription factor EB (tfeb) (Figure 4F), whose elevated levels is a further indicator of dormant cell (García-Prat et al, 2021;Garcia Prat et al, 2020).…”
Section: Increased Activation Of Retinoic Acid Receptor Rarα In the Agmmentioning
confidence: 64%